Biodegradation of expanded polystyrene with isolated intestinal microbiota from Tenebrio molitor (Tenebrionidae) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
The research project was carried out using biotechnology as an alternative solution for a problem that is still difficult to solve, such as the biodegradation of single- use plastics. The objective was to isolate bacteria from the intestinal microbiota of Tenebrio molitor larvae as organisms that degrade expanded polystyrene, to identify the genus of isolated bacteria, to determine the volume of polystyrene consumed by the larvae as their sole source of food, under laboratory conditions, and finally assess the biochemical composition of the waste generated as part of the digestion process of Tenebrio molitor larvae.